Health-Related Quality of Life, Psychosocial Distress and Unmet Needs in Older Patients With Head and Neck Cancer - McDowell, Lachlan; Rischin, Danny; Gough, Karla; Henson, Christina (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is the most common cancer involving the mucosal surfaces of the head and neck and is associated with a number of etiological factors, including cigarette smoking, alcohol and betel nut consumption and exposure to high-risk human papillomavirus. The risk of HNSCC increases with age, peaking in the seventh and eighth decade, but this varies by anatomical and histological subtype. While several advancements have been made in the treatment of head and neck cancer (HNC) in recent decades, undertaking curative treatment still subjects the majority of HNSCC patients to substantial treatment-related toxicity requiring patients to tolerate a gamut of physical, psychological, and emotional demands on their reserves. In conjunction with other patient-related factors, clinicians involved in treating patients with HNSCC may incorporate advancing chronological age into their decision-making process when determining treatment recommendations. While advancing chronological age may be associated with increased concerns regarding physical treatment tolerability, clinicians may also be concerned about heightened vulnerability in various health and wellbeing outcomes. The available literature, however, does not provide evidence of this vulnerability in patients with advancing age, and, in many instances, older patients self-report greater resilience compared to their younger counterparts. While this data is reassuring it is limited by selection bias and heterogeneity in trial and study design and the absence of a consistent definition of the elderly patient with HNSCC. This narrative review article includes a review of the measures used to assess HRQL, psychosocial outcomes and unmet needs in elderly or older patients with HNSCC.